Management of Pediatric Elbow Fractures and Dislocations - Marko Bašković; Domagoj Pešorda; Luca Zaninović; Damir Hasandić; Katarina Lohman Vuga; Zenon Pogorelić (MDPI AG, 2024)
Pediatric elbow fractures and dislocations have always been a challenge from a diagnostic and therapeutic point of view, primarily due to the complex nature of the pediatric elbow, especially its developmental anatomy. They must be diagnosed and treated on time to prevent numerous complications with long-term consequences. With the development of radiology and pediatric surgery and orthopedics, as well as the development of modern osteosynthesis materials, concerning current scientific and professional knowledge, the outcomes are getting better, with fewer acute and chronic complications. This comprehensive review aims to provide clinicians current knowledge about pediatric elbow fractures and dislocations so that in daily practice they have as few doubts as possible with the best possible treatment outcomes.